Moral distress among critical care nurses before and during the COVID-19 pandemic: A systematic review - Beheshtaeen, Fatemeh (Nursing ethics, 2024)
Moral distress has emerged as a significant concern for critical care nurses, particularly due to the complex and demanding care provided to critically ill patients in critical care units. The ongoing COVID-19 pandemic has introduced new ethical challenges and changes in clinical practice, further exacerbating the experience of moral distress among these nurses. This systematic review compares the factors influencing moral distress among critical care nurses before and during the COVID-19 pandemic to gain a comprehensive understanding of the impact of the pandemic on moral distress. For this systematic review, PubMed, Scopus, ProQuest, Web of Science, medRxiv, bioRxiv, Embase, and Google Scholar were all utilized in the search. The search covered articles published from 2012 to December 2022, encompassing a 10-year timeframe to capture relevant research on moral distress among critical care nurses. In total, 52 articles were included in this systematic review. The findings indicate that personal, caring-related, and organizational factors can influence nurses' moral distress. Before the pandemic, factors including futile and end-of-life care, conflicts with physicians, nurse performance and authority, poor teamwork, decision-making regarding treatment processes and patient care, limited human resources and equipment, medical errors, patient restraints, and nurses' age and work experience affect critical care nurses' moral distress. Similarly, during the COVID-19 pandemic, factors contributing to moral distress include futile and end-of-life care, fear of contracting and spreading COVID-19, decision-making about treatment processes, poor teamwork, and being female. This study revealed that the factors contributing to moral distress were approximately similar in both periods. Futile care and end-of-life issues were critical care nurses' primary causes of moral distress. Implementing prevention strategies and reducing these underlying factors could decrease this major issue and improve the quality of care.